ChemInform Abstract: Carbolithiation of S‐Alkenyl‐N‐aryl thiocarbamates: Carbanion Arylation in a Connective Route to Tertiary Thiols. Issue 33 (25th July 2013) - Castagnolo, Daniele; Foley, Daniel J.; Berber, Hatice; Luisi, Renzo; Clayden, Jonathan
Abstract S‐Alkenyl‐N‐arylthiocarbamates undergo carbolithiation with a range of organolithium reagents, generating benzyllithium intermediates in a stereospecific manner which may undergo N to C aryl migration to yield thiocarbamates with tertiary substituents.